The Stockholm bloodbath of 1520
1 online resource.
Keywords: The Stockholm Bloodbath on November 7-9, 1520, during which Kristian II had more than 100 persons executed on charges of heresy, is a turning point in the history of the Northern kingdoms. This bloodbath eventually led to Kristian II's lifelong incarceration, the rise of the Swedish Vasa dynasty, and the end of the Kalmar Union. It has commonly been perceived both as part of Swedish-Danish conflict and also as part of a Swedish civil war. In this volume, fifteen researchers offer new insights both into the events themselves and also, most significantly, into their background and aftermath, which stretch far beyond Stockholm and the year 1520.